Clinical Landmarks of COVID-19 in Newborn, Children and Teenagers - Stefan, Bittmann; Elisabeth, Luchter; Gloria, Villalon; Elena, Moschüring-Alieva; Anne, Weissenstein (Journal of Pediatric Health And Nutrition, 2020)
This review catalogs clinical landmarks of COVID‑19 across newborns, children, and adolescents, including MIS‑C, risk factors, and considerations for vaccination and school policies.
Keywords: COVID-19